ULTRASTRUCTURAL PROPERTIES OF THE ADRENAL GLANDS DURING THE ACUTE HYPOXIA (World Science, 2019)
The goal of the study was to study the morphofunctional properties of ultrastructural changes in the cellular and extracellular structures of the adrenal glands during hypobaric hypoxia. The materials of the study were 30 male white rats weighing 180-200 grams. Thus, the results of the conducted studies showed that morphofunctional changes under the effects of acute hypoxia, which develop in different zones of the adrenal cortex, also change the histofunctional state of the adrenal medulla. Morphometric indicators of the adrenal parenchyma increase from the 5th day of hypoxia and are characterized by the increased blood supply to the adrenal glands, which occurs both by the dilatation of capillaries and by an increase in their density.